Mainstreaming One Health approaches and principles into research in Ethiopia: Guidelines, frameworks and ethical procedures - Hadush, B.; Ambalu, A.; Gumi, B.; Tadesse, Y.; Mor, Siobhan M.; Mutua, Florence K.; Richards, Shauna; Kaba, M. (International Livestock Research Institute, 2024)
One Health is a collaborative, multisectoral and transdisciplinary approach that recognizes the interdependence of humans, animals, plants and their shared environment, with the goal of enhancing health outcomes at the local and global levels. The Capacitating One Health in Eastern and Southern Africa (COHESA) project aims to empower research and academic institutions to nurture the next generation of One Health researchers by creating tailored tools adaptable to local contexts. In Ethiopia, this includes development of One Health research guidelines to provide a structured framework for conducting research, emphasizing the integration of different disciplines to tackle health challenges at the intersection of the human, animal and ecological realms.